1995
DOI: 10.1113/jphysiol.1995.sp020717
|View full text |Cite
|
Sign up to set email alerts
|

Dual modulation of synaptic inhibition by distinct metabotropic glutamate receptors in the rat hippocampus.

Abstract: 1. The effects of metabotropic glutamate receptor (mGluR) activation on synaptic inhibition were examined using whole-cell recordings of spontaneous and miniature inhibitory synaptic currents from CA3 pyramidal cells in rat hippocampal slices.2. The mGluR agonist (1S, 3R)trans-i-aminocyclopentane-1,3-dicarboxylic acid (tACPD) increased spontaneous IPSC (spIPSC) frequency by up to 5-fold. At doses above 5/AM the increase was transient (15-45 s) and was followed by a decline to control frequency. In these condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 42 publications
7
83
0
Order By: Relevance
“…In the presynaptic active zone of glutamatergic boutons, mGluR8 is probably an autoreceptor regulating glutamate release (Baskys and Malenka, 1991;Desai et al, 1994;Gereau and Conn, 1995;Scanziani et al, 1998), whereas in GABAergic terminals, it may regulate heterosynaptically GABA release (Gereau and Conn, 1995;Poncer et al, 1995;Morishita et al, 1998;Semyanov and Kullmann, 2000;Kogo et al, 2004). We have shown recently that at 50 M L-AP-4 depressed IPSCs in oriens/ alveus interneurons, including identified O-LM cells (Kogo et al, 2004), consistent with the activation of mGluR8 (Wu et al, 1998;Schoepp et al, 1999;Rosemond et al, 2002).…”
Section: The Role Of Group III Mglurssupporting
confidence: 60%
“…In the presynaptic active zone of glutamatergic boutons, mGluR8 is probably an autoreceptor regulating glutamate release (Baskys and Malenka, 1991;Desai et al, 1994;Gereau and Conn, 1995;Scanziani et al, 1998), whereas in GABAergic terminals, it may regulate heterosynaptically GABA release (Gereau and Conn, 1995;Poncer et al, 1995;Morishita et al, 1998;Semyanov and Kullmann, 2000;Kogo et al, 2004). We have shown recently that at 50 M L-AP-4 depressed IPSCs in oriens/ alveus interneurons, including identified O-LM cells (Kogo et al, 2004), consistent with the activation of mGluR8 (Wu et al, 1998;Schoepp et al, 1999;Rosemond et al, 2002).…”
Section: The Role Of Group III Mglurssupporting
confidence: 60%
“…(Staub, Vranesic & Knopfel, 1992;McBain, DiChiara & Kauer, 1994;Shirasaki, Harata & Akaike, 1994;Poncer, Shinozaki & Miles, 1995). A number of other responses induced by stimulation of mGluRs, such as the reduction in a leak K+ conductance, did not fade with prolonged agonist application (Fig.…”
Section: Hippocampal Slice Culturesmentioning
confidence: 89%
“…Immunohistochemical studies have found mGluR1 to be highly enriched on the soma and dendrites of somatostatin-containing inhibitory interneurons in hippocampus (Baude et al 1993;Ferraguti et al 2004;Hampson et al 1994) as well as on other interneuron subtypes (Ferraguti et al 2004). Activation of group I mGluRs increases the excitability of GABAergic interneurons, both in hippocampus (Mannaioni et al 2001;Mori and Gerber 2002;Poncer et al 1995;Yanovsky et al 1997) and in other brain regions (Chu and Hablitz 1998;Zheng and Johnson 2003). This can cause an increase in the release of GABA (Chu and Hablitz 1998;Mannaioni et al 2001;Mori and Gerber 2002), thus increasing inhibition of pyramidal cells.…”
Section: Location Of Mglur1 Receptors That Reduce Short-term Facilitamentioning
confidence: 99%